Treatment of intracapsular fractures of the proximal femur with bipolar hemiarthroplasty in patients under the age of 70: clinical and radiographic results at mean 20 years follow-up - Murena, Luigi; Fattori, Roberto; Scamacca, Veronica; Cau, Paolo; Ratti, Chiara; Canton, Gianluca (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: Hemiarthroplasty (HA) for femoral neck fractures in relatively young patients has been reported to have poor results. Moreover, cotyloiditis has been described for HA as a possible cause of revision. Nontheless, in the literature there is lack of studies specifically evaluating this topic, particularly in relatively young patients. Aim of the study was to evaluate bipolar HA clinical and radiographic results at long term follow up in patients treated under the age of 70. Methods: Study population counted 137 patients treated between 1990 and 2000. In 2015 alive patients who did not undergo implant revision were clinically evaluated. Harris Hip Score and EQ-5D questionnaire were administrated. Acetabular erosion was identified and classified on follow-up radiographs. Results: At follow-up there were 39 living patients, mean age 64, 80.5% women. 3 patients were not traceable. Revision rate was 32% (12/37), because of cotyloiditis in 2 cases. In the 22 non-revised patients at mean 20 years follow up 3 cases presented moderate to severe acetabular erosion. Mean HHS and EQ values were 73.23 and 0.527 respectively. Conclusions: Bipolar HA provided satisfying results in relatively young patients at long term follow-up. In the present study age turned out to be the most relevant variable to influence results. Data suggest that acetabular erosion might have a secondary role in determining both the implant’s survival and the long term clinical results.